Nilai-nilai Pendidikan Akhlak dalam Q.S Al-Qasash ayat 77 - Lani Nurpratiwi; Nan Rahminawati; Helmi Aziz (Bandung Conference Series: Islamic Education, 2024)
Abstract. The development of an increasingly advanced economy encourages people to seek worldly satisfaction and forget about the eternal life of the afterlife. The Qur'an as a guide to life teaches how Muslims should behave in seeking and spending their wealth, namely by avoiding bad behavior, which can damage and harm other people and themselves, just like Qarun, who is an example of human behavior with bad morals. The focus of the discussion in this research is regarding the values of moral education. By classifying the opinions of mufassir, drawing out the essence, classifying the opinions of experts about moral education and finding the values of moral education in Q.S Al-Qasash verse 77. This research uses a qualitative approach, using library study data collection techniques, and analyzed using the tahlili method. The case of human greed in using their wealth is a sign of moral decline and acts of destruction on the face of the earth, such as the behavior of israf, tabdzir and stinginess carried out by Qarun today. It is hoped that the moral education values contained in Q.S Al-Qasash verse 77 can be applied in everyday life. Abstrak. Geliat perekonomian yang semakin maju mendorong seseorang mencari kepuasan duniawi dan melupakan kehidupan akhirat yang kekal. Al-Qur’an sebagai pedoman hidup mengajarkan bagaimana seharusnya perilaku muslim dalam mencari dan membelanjakan hartanya yaitu dengan menjauhi perilaku yang buruk, yang dapat merusak dan merugikan orang lain serta dirinya sendiri seperti halnya Qarun yang merupakan contoh perilaku manusia yang memiliki akhlak yang buruk. Fokus pembahasan pada penelitian ini mengenai nilai-nilai pendidikan akhlak. Dengan Mengklasifikasikan pendapat mufassir, Menarik esensi, Mengklasifikasikan pendapat para ahli tentang pendikan akhlak dan Menemukan nilai-nilai pendidikan akhlak dalam Q.S Al-Qasash ayat 77. Penelitian ini menggunakan pendekatan kualitatif, dengan teknik pengumpulan data studi kepustakan, dan dianalisis dengan metode tahlili. Kasus keserakahan manusia dalam menggunakan hartanya merupakan salah satu tanda dari kemerosotan akhlak dan perbuatan kerusakan di muka bumi, seperti perilaku israf, tabdzir dan kikir yang dilakukan para Qarun saat ini, diharapkan nilai-nilai pendidikan akhlak yang terkandung dalam Q.S Al-Qasash ayat 77 dapat diterapkan dalam kehidupan sehari-hari.